«Being creative» A necessary sensitivity for the world of work? - Quattrini, Diego (2021)
Introduction: We see in work processes emotional demands that are incorporated in the practic sense of men and women worker. The study examines the configuration of the feelings for the work of various local entrepreneurs (Villa María, Córdoba). To do this, it reflects on their quirement creativity. Objective: The exhibition proposal is to show the relationships there are established in the constitution of the work force and the incidence of creative attitude as a pedagogical action generated from the conditions presented by the structure of current capitalism. Method and technique: As a methodology to nárrate the creative, a virtual interview («WhatsApp interviews») will be implemented, for entrepreneurs where their expressivenessn is privileged, assuming their limits and possibilities. Results: As a result, it was observed in the narratives a material/emotional body that sustains the constitution of the creative. Conclusions: Hence, it is concluded that the existence of this attitude promotes a rational/individual effort that is rebuilt within the framework of a political economy of morality based on the assumption of enjoyment and endurance.